New Media and Social Construction of Technology (SCOT) on Cak Ed Online Delivery Service in Lamongan Regency (MUHARRIK: Jurnal Dakwah dan Sosial, 2021)
The study analyzes Cak Ed's online delivery service in Lamongan using SCOT (Social Construction of Technology) theory. The data collection method in this study used observations on social media and interviews. SCOT theory is relevant for analyzing technological developments as social constructions in society. The development of information and communication technology is influenced by how the community can innovate to create new things through technology. The presence of communication technology in terms of transportation for online delivery services, Cak Ed Delivery, in Lamongan Regency is a real example of the implementation of social construction in society and new media. This study indicates that Cak Ed Delivery as local online transportation in Lamongan Regency can compete and develop forward as a solution to overcome the problems of the people of Lamongan Regency in terms of transportation and shopping in an easy, cheap, fast, safe, and comfortable way.